"Mainstreaming" foresight program development in the public sector. Issue 5 (5th September 2019) - Janzwood, Scott; Piereder, Jinelle
Abstract : Purpose: This paper aims to develop a framework for benchmarking the maturity of public sector foresight programs and outlines strategies that program managers can use to overcome obstacles to foresight program development in government. Design/methodology/approach: The public sector foresight benchmarking framework is informed by a bibliometric analysis and comprehensive review of the literature on public sector foresight, as well as three rounds of semi-structured interviews conducted over the course of a collaborative 18-month project with a relatively young department-level foresight program at the government of an Organisation for Economic Co-operation and Development (OECD) country. The paper frames public sector organizations as "complex adaptive systems" and draws from other government initiatives that require fundamental organizational change, namely, "gender mainstreaming". Findings: Nascent or less mature programs tend to be output-focused and disconnected from the policy cycle, while more mature programs balance outputs and participation as they intervene strategically in the policy cycle. Foresight program development requires that managers simultaneously pursue change at three levels: technical, structural and cultural. Therefore, successful strategies are multi-dimensional, incremental and iterative. Originality/value: The paper addresses two important gaps in the literature on public sector foresight programs by comprehensively describing the key attributes of mature and immature public sector foresight programs, and providing flexible, practical strategies for program development. The paper also pushes the boundaries of thinking about foresight by integrating insights from complexity theory and complexity-informed organizational change theory.